Accounting for the Duality of the Italian Economy - Jesús Fernández-Villaverde; Dario Laudati; Lee Ohanian; Vincenzo Quadrini (Center for Economic Studies and ifo Institute (CESifo), 2023)
After 162 years of political unification, Italy still displays large regional economic differences. In 2019, the per capita GDP of Lombardia was 39,700 euros, but Calabria's per capita GDP was only 17,300 euros. We build a two-region, two-sector model of the Italian economy to measure the wedges that could account for the differences in aggregate variables between the North and the South. We find that the largest driver of the regional disparity in per capita output is the difference in total factor productivity, followed by fiscal redistribution. These two factors, together, account for more than 70 percent of the output disparity between the North and the South.
Keywords: E10; E60; 330; Italian economy; macroeconomic wedges; regional fiscal redistribution; regional convergence